1980
DOI: 10.1111/j.1751-1097.1980.tb04004.x
|View full text |Cite
|
Sign up to set email alerts
|

Phototoxic Effects of Naturally Occurring Polyacetylenes and Α‐terthienyl on Human Erythrocytes

Abstract: Abstract— Hemolysis, K+ leakage and acetylcholinesterase (AChE) inhibition in human erythrocytes were observed with certain naturally occurring polyacetylenes and a thiophene derivative, α‐terthienyl. K' leakage, subsequent hemolysis and AChE inactivation by phenylheptatriyne (PHT), a phototoxic compound, were considerably enhanced by UV light (312–400 nm). The same was true with α‐terthienyl and with certain other polyacetylenes. Oxygen enhanced AChE inactivation and hemolysis with α‐terthienyl in light. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
1

Year Published

1980
1980
1992
1992

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(20 citation statements)
references
References 14 publications
2
17
1
Order By: Relevance
“…New alkaloids containing 6, 7, and 8 N-methyltryptamine units were recently identified in another genus of Rubiaceae (9). The study of their cytotoxic properties on HTC cells could give additional results to verify our hypothesis.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…New alkaloids containing 6, 7, and 8 N-methyltryptamine units were recently identified in another genus of Rubiaceae (9). The study of their cytotoxic properties on HTC cells could give additional results to verify our hypothesis.…”
supporting
confidence: 53%
“…One can also suggest that the observed cytotoxic analogies between the pairs EIC and D/B could be due to an identical position of the C-C bond in each pair of compounds (Fig. 1).New alkaloids containing 6, 7, and 8 N-methyltryptamine units were recently identified in another genus of Rubiaceae (9). The study of their cytotoxic properties on HTC cells could give additional results to verify our hypothesis.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Thus, the geomet- ric advancement in the anal gill functions could be a justification for the increase in the specific SOD activity after every molt. It has been shown that a-terthienyl is lethal to a host of living systems including microorganisms [5-71 and human erythrocytes [22,23]. The plasma membrane and the membrane proteins are thought to be primary targets of the a-terthienyl toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Methods for the isolation of 7-phenylhepta 2,4,6-triyne (PHT) and the synthesis of a-terthienyl (a-t) have been described by Wat et al (1980). Stock solutions of PHT and a-t at 0.1% in 95% ethanol were used.…”
Section: Methodsmentioning
confidence: 99%